PENGARUH PROFITABILITAS, PERTUMBUHAN ASSET, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL (STUDY KASUS PADA PERUSAHAAN REALESTATE DAN PROPERTY YANG TERDAFTAR DI BEI TAHUN 2013 – 2015) - Harahap, Aderina K; Irawan, Arif Eka (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2018)
The purpose of this study is to investigate the Profitability, Asset Growth, and Firm Size to Corporate Capital Structure . This study focused on Property and Real estate companies listed in Bursa Efek Indonesia for period 2013-2015. This research is using quatitative and purposive sampling method in order to collect the sample. Based on certain criteria, there were 24 properties and real estate companies that matched with the sample. The statistical method used in this study is multiple regression. The simultaneous testing showed that Profitability, Asset Growth, and Firm Size are influenced to Capital Structure Keywords - Corporate capital structure, profitability, asset growth, firm size